Direct bonding of silicon carbide with hydrofluoric acid treatment for high-temperature pressure sensors. Issue 3 (15th February 2020) - Li, Jian; Jiang, Yonggang; Li, Hongchang; Liang, Xiaobo; Huang, Manguo; Liu, Defeng; Zhang, Deyuan
Abstract: Direct bonding of single-crystal silicon carbide (SiC) is a critical process for the fabrication of pressure sensors used in harsh environments. In this paper, we present a direct bonding process with a surface treatment using hydrofluoric acid to remove the oxide on the SiC surface and eliminate the oxide interlayer between the bonded SiC wafers. After direct bonding with hydrofluoric acid treatment, the oxide interlayer is almost invisible in the field emission scanning electron microscope and energy dispersive spectrometry analyses. The bonding strengths of the SiC samples bonded under various bonding temperatures and bonding times are evaluated. Compared to the sample with an oxide interlayer, the bonding strength obtained with direct bonding is improved by 49%. The maximum bonding strength reaches 6.96 MPa with a bonding temperature of 1100 °C, a uniaxial pressure of 50 MPa, and a bonding time of 4 h. In addition, the vacuum tightness of the bonded cavity was also investigated, and the results indicate that the vacuum sensor cavity was effectively sealed with the direct bonding method.